The Meaning of ‘Environment’ in the German Legal Order - Hoffmann, Jan (University of Wroclaw. Faculty of Law, Administration & Economics, 2014)
The definition of the term ‘environment’ is a key issue in environmental law. The broader the definition, the wider the field of environmental law. In order to substantiate the term, some legal orders define it comprehensively, while others do not. In the absence of an Environmental Law Code (Umweltgesetzbuch), the German legal order does not. However, with judicial means of interpretation the author analyses the German understanding of the term. As a result the author concludes that ‘environment’ in Germany at present means: medial – water, soil and atmospheric air; vital – humans, animals and plants; natural-cultural – landscapes; objective – certain material property, and integrative – the observance of the interaction between these components. As a comparative interpretation of the term indicates, this meaning is consistent with European Union environmental law.
Keywords: Niemcy; prawo ochrony środowiska